2012
DOI: 10.3354/meps09604
|View full text |Cite
|
Sign up to set email alerts
|

Ontogenetic niche changes in haddock Melanogrammus aeglefinus reflected by stable isotope signatures, δ13C and δ15N

Abstract: We investigated stable nitrogen (δ 15 N) and carbon (δ 13 C) isotope signatures in haddock Melanogrammus aeglefinus in Ullsfjord, Norway, and found evidence of an ontogenetic shift as a result of growth but in the absence of other morphological changes. Stable isotope signatures and trophic level (TL) changed significantly from a pelagic signature and a low TL to a more benthic associated signature and higher TL when the fish were ca. 20 cm in length. The stable isotope signatures of haddock were compared with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…Albert (1995) observed that small haddock fed also on pelagic prey in the North Sea off southwestern Norway. Ramsvatn and Pedersen (2012) also found a significant difference in δ 13 C and δ 15 N compositions between small and large haddock in the Norwegian Sea off northern Norway.…”
Section: Cod and Haddock: Strong Dependence On The Benthic Trophic Pamentioning
confidence: 72%
See 1 more Smart Citation
“…Albert (1995) observed that small haddock fed also on pelagic prey in the North Sea off southwestern Norway. Ramsvatn and Pedersen (2012) also found a significant difference in δ 13 C and δ 15 N compositions between small and large haddock in the Norwegian Sea off northern Norway.…”
Section: Cod and Haddock: Strong Dependence On The Benthic Trophic Pamentioning
confidence: 72%
“…In the deep zone, however, small individual's trophic position was clearly lower than the large one and showed no SEAc overlap, indicating a probable ontogenetic shift. Ramsvatn and Pedersen (2012) found a gradual change in cod's isotopic composition with size. Similarly, Du Buit (1995) found an increase in fish items in the diet of cod as cod size increased in the Celtic Sea, as did Hüssy et al (2016) for the North Sea.…”
Section: Cod and Haddock: Strong Dependence On The Benthic Trophic Pamentioning
confidence: 95%
“…2 cm 3 ) were dissected from the left dorsal side of the fish and worked up according to standard procedures before each sample was placed in a drying oven for 48 h at 62°C (Ramsvatn and Pedersen 2012). The muscle samples (A. atlanticus, n = 18; M. scorpius, n = 8; L. decagonus, n = 9) were submitted for analysis (without lipid correction) by the Stable Isotopes in Nature Laboratory (SINLAB), Rivers Institute, Canada.…”
Section: Stable Isotope Analysismentioning
confidence: 99%
“…TL estimates for each species were determined based on calculations of the dietary enrichment in isotopic nitrogen (d 15 N) up the food chain (Peterson and Fry 1987;Ramsvatn and Pedersen 2012).…”
Section: Stable Isotope Analysismentioning
confidence: 99%
See 1 more Smart Citation